Development of Augmented Reality (AR) Based Trompong - Danandjaya, Gede Bagus; Wibawa, I Gede Arta (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 3 (2021): JELIKU Volume 9 No 3, Februari 2021, 2021)
In gamelan, one of the most important instruments is trompong. Trompong is an idiphones instrument that has 10 rows of round shaped metal called pencon. Every pencon has its own sound. As a traditional music instrument, of course gamelan especialy trompong must be preserved continuously. But unfortunately, playing Balinese gamelan with real instrument is hard to do because the difficulty to finding gamelan in the real world. By using technolgy such as Augmented Reality, playing trompong possible to do even without having the real instrument.  Augmented Reality will be develop using Unity 3D software along with Vuforia SDK, and also this application using Android smartphone as a base of Augmented Reality application. This Augmented Reality application called TrompongAR and will be marker based Augmented Reality, by using a target marker will help Augmented Reality to place where the 3-dimensional trompong will placed. The 3-dimensional trompong will have 10 pencon that can played by tapping the pencon, the touched pencon will produce sound like the real instrument.